Distribuição, abundância e hábito alimentar de Asteroidea (Echinodermata) de fundos inconsolidados da Plataforma Continental do Cabo Frio, RJ - Ventura, Carlos Renato Rezende (1991)
This study is part of the Cabo Frio Upwelling Ecosystem Integrated Project and aims to verify the specific composition, distribution and diets of asteroids of the Cabo Frio continental shelf, RJ. Asteroide were collected monthly from January 1986 to December 1988 by a 10 m otter-trawl. Twenty minute hauls were done along the 30, 45 and 60 m isobates off Maçambaba Beach. Water and sediment samples were obtained at each depth. Prey denaities were assessed by a Van-Veen grab (0, 1 m2 ) in January, 1988. Asteroids were measured, weighed and aborally cut to analyse the stomach contents. Colder water (below 18°C) was observed, mainly during the summer. Sediment changed according to the depth: medium sand at 30 m to fine sand at 60 m. Five species were collected: Astropecten cingulatus Sladen, 1889, A. armatus brasiliensis Müller & Troschel, 1842, Luidia ludwigi scotti Bell, 1917, L. alternata (Say, 1825) and Tethyaster vestitus (Say, 1825). The first three were the most frequent and abundant. Species bathymetrical distribution presented different patterns: A. armatus brasiliensis was more abundant at 30 m, A. cingulatus at 60 m, but at 45 m the three species coexisted with similar numbers. The highest densities were observed during the upwelling periods. Asteroid diets were significantly different both at each depth and among species at 45 m, where they coexist. The results suggest a partition of feeding resources, mainly at 45 m. Intraspecific diet differences were lese evident at 30 and 60 m. A. armatus brasiliensis showed a larger niche breadth. The feeding niche of A. cingulatus seems to be part of A. armatus brasiliensis niche. L. ludwigi scotti showed a smaller feeding spectrum, eating mainly Abra lioica. The potential competition among species is suggested, but was not possible to confirm. Experimental manipulations are necessary to test the hypotheses arisen related to partition of feeding resources.